Development and Effectiveness of the Snake Adventure Board Game to Enhance Learning Interest and Outcomes in Bhinneka Tunggal Ika Instruction (JED (Jurnal Etika Demokrasi), 2025)
This study addresses the persistent challenges in fostering student engagement and learning outcomes in Bhinneka Tunggal Ika instruction, highlighting the need for innovative and interactive educational media. The research aims to develop and evaluate the effectiveness of the Snake Adventure board game as a technology-enhanced, pedagogically robust learning tool. Employing a research and development design structured by the ADDIE model, the study involved secondary school students as subjects and utilized both expert validation and classroom implementation. Data were analyzed using descriptive and inferential statistics, supported by qualitative feedback from participants. The findings reveal that the Snake Adventure board game demonstrated high validity and feasibility, with significant improvements observed in both student motivation and academic performance. The intervention resulted in notable increases in learning interest and achievement scores, affirming the efficacy of game-based, multimodal approaches in civic education. In conclusion, the board game offers a practical and empirically supported solution to enhance student engagement and outcomes in multicultural instruction. The originality of this study lies in its integration of TPACK principles and participatory design, distinguishing it from prior research in the field. This research contributes meaningfully to the advancement of educational innovation, providing a replicable model for developing impactful instructional games in diverse learning contexts.
Keywords: Snake Adventure Board Game; Bhinneka Tunggal Ika Instruction; Game-Based Learning; Student Motivation; TPACK Integration